Effect of C/N ratio and starch concentration on ethanol production from sago starch using recombinant yeast - Abd‐Aziz, S.; Ang, D.C.; Yusof, H.M.; Karim, M.I.A.; Ariff, A.B.; Uchiyama, K.; Shioya, S. (2001)
Recombinant Saccharomyces cerevisiae YKU 131 (capable of expressing glucoamylase) was used to produce ethanol from sago starch. The optimum C/N ratio for ethanol production by the recombinant yeast was 7.9, where 4.7 and 10.1 g/l ethanol was produced from 20 and 40 g/l sago starch, respectively. At sago starch concentration higher than 40 g/l and C/N ratio higher than 10.4, glucoamylase production and rate of starch hydrolysis were reduced, which in turn, reduced ethanol production significantly. The theoretical yield of ethanol based on sago starch consumed in fermentation using 40 g/l was 72.6%. This yield was slightly lower than those obtained in fermentation using soluble starch such as potato and corn starch, which ranged from 80-90% as reported in the literature. However, S. cerevisiae YKU 131 could only utilize 62% of the total amount of starch added to a medium.